MELT LOSS DAN POROSITAS PADA ALUMINIUM HASIL DAUR ULANG - Fahmi Fasya; Norman Iskandar (JURNAL TEKNIK MESIN, 2015)
Aluminum is a lightweight metal, resistant to corrosion, strong, and easy to get, so its use increasing as a basic material. The accumulation of aluminum scrap that not treated properly can pollute the environment, so need effort to recycle aluminum scrap that can be recovered into new products. Recycling aluminum is profitable in terms of economical, because if these metals are extracted from ore of aluminum is very expensive, pollute the environment, consume large amounts of energy and recycled aluminum becomes the cycle that can occur repeatedly without loss of its properties. Utilization recycling is done through the casting process. Aluminum casting process must be carried out carefully to avoid defective products, one of the most commond efect is porosity. Therefore, it needs to do testing to calculate the porosity in order to improve the quality of casting products. The analysis is using materials from recycled aluminum from beverage cans, household appliances, wheels, and the engine block that cast using sand casting method. Comparisons is 1 kg for each casting. Tests were carried out with density test and then perform calculations to determine the porosity and melt loss. The results of the study showed the highest porosity is specimen from beverage cans with 11,94 % of porosity and density value at 2.58 g/cm3,  followed scrap from wheels with 2.61 g/cm3 density which 10.92% porosity. For porosity scrap from household appliances and engine block, is 7.16% and 5.64%. As for the lowest percentage melt loss is scrap from wheel with percentage 14%. And the highest melt loss is scrap from beverage cans with percentage 18%.